X-ray photoelectron spectroscopy: a surface characterization technique - Hortigüela Gallo, María J. (2019)
During the last years, an increasing number of students have visited the XPS laboratory for characterizing their samples with this experimental technique. Their background span over a wide range of fields such as physics, material science, chemistry and biology, among others. For most of them, both XPS and ultra-high vacuum technology were something new and they needed help to deal with the data of their samples. This book tries to concentrate the key information that a young researcher needs for a first approach to XPS. We hope the students will understand its working principle and will obtain the basic tools for analysing their data.